2003
DOI: 10.1128/jb.185.1.381-385.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Helix-Turn-Helix Motif of Bacillus thermoglucosidasius HrcA Essential for Binding to the CIRCE Element and Thermostability of the HrcA-CIRCE Complex, Indicating a Role as a Thermosensor

Abstract: In the heat shock response of bacillary cells, HrcA repressor proteins negatively control the expression of the major heat shock genes, the groE and dnaK operons, by binding the CIRCE (controlling inverted repeat of chaperone expression) element. Studies on two critical but yet unresolved issues related to the structure and function of HrcA were performed using mainly the HrcA from the obligate thermophile Bacillus thermoglucosidasius KP1006. These two critical issues are (i) identifying the region at which Hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Thus, an increased temperature alone is not sufficient for the chlamydial heat shock response, suggesting that additional factors that are not present in our in vitro system play a role. Studies of the thermostability of HrcA-CIRCE complexes in other bacteria have shown that HrcA dissociates from CIRCE at temperatures above physiologic temperatures (24,55), although this effect varies with the bacterial species (14) and the presence of additional factors (24,38). C. trachomatis is an obligate intracellular parasite and, as such, is exposed to a narrower range of growth temperatures than the free-living, gram-positive bacteria in which much of HrcA activity has been characterized previously.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an increased temperature alone is not sufficient for the chlamydial heat shock response, suggesting that additional factors that are not present in our in vitro system play a role. Studies of the thermostability of HrcA-CIRCE complexes in other bacteria have shown that HrcA dissociates from CIRCE at temperatures above physiologic temperatures (24,55), although this effect varies with the bacterial species (14) and the presence of additional factors (24,38). C. trachomatis is an obligate intracellular parasite and, as such, is exposed to a narrower range of growth temperatures than the free-living, gram-positive bacteria in which much of HrcA activity has been characterized previously.…”
Section: Discussionmentioning
confidence: 99%
“…Lund and I. Barber, unpublished data). HrcA instability at elevated temperatures leads to dissociation of HrcA from the CIRCE element which causes increased expression of heat-shock genes (Watanabe et al 2001;Hitomi et al, 2003). A feedback loop involving GroES and GroEL acts to fold HrcA to its active conformation under non-heat-shock conditions (Mogk et al, 1997;Reischl et al, 2002;Roncarati et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…4A) constitutes the recognition helix of the HrcA proteins. The same region was recently proposed as the recognition helix of HrcA for Bacillus thermoglucosidasius and B. subtilis (19,36). Figure 4A also shows the putative stabilization helix of the HTH motif (amino acids 42 to 48 in C. crescentus) in the various HrcA proteins.…”
Section: Resultsmentioning
confidence: 93%